Unraveled role of TLR7-mediated interferon signaling activation in COVID-19 - Xue, Junjian; Wang, Xiaoyin; Wang, Hui; Qiao, Bin; Gao, Pengfei; Ren, Bin; Yan, Shushan (Frontiers in Cellular and Infection Microbiology, 2025)
Emerging evidence underscores the critical role of Toll-like receptor 7 (TLR7)-mediated interferon (IFN) signaling in host defense against viral infections including SARS-CoV-2, through the modulation of both innate and adaptive immunity. However, the specific mechanisms by which TLR7 activation shapes SARS-CoV-2-specific immune responses, particularly via IRF-IFN pathways, remain incompletely elucidated. This review synthesizes current findings on how intrinsic TLR7-driven IFN signaling influences viral clearance, modulates adaptive immunity, and contributes to autoantibody production in COVID-19. A deeper understanding of these processes is essential for developing targeted therapeutic interventions and improved vaccines aimed at mitigating severe COVID-19 and preventing post-acute sequelae of SARS-CoV-2 infection (PASC).